Personalidad y Ansiedad en Deportistas de Judo. Federación Deportiva de Chimborazo, 2019 - Viteri Vallejo, Raúl Antonio (2019)
The present research work with the topic: PERSONALITY AND ANXIETY IN JUDOKAS to “THE SPORTING FEDERATION OF CHIMBORAZO” in 2019. It takes as a starting point the personality and precompetitive anxiety variables presented in these individuals. This study aims to analyze the personality and precompetitive anxiety in judo athletes from “THE SPORTING FEDERATION OF CHIMBORAZO”. Only few extensive studies related to this subject have been written in our sporting context which also includes the sporting environment of the province of Chimborazo. This research implies a reason for motivation and transcendence for the optimal development of judo and other sports disciplines nationwide. Regarding the applied methodology, the study was focused on the quantitative approach for being measurable through psychological tests such as "Seapsi Personality Questionnaire" and "Precompetitive Anxiety Test-Revised Version (Csai-2r)". The mentioned tests were applied in a non-probabilistic sample, for convenience, to 17 judokas of legal age. In order to collect and tabulate the data a spreadsheet and the statistical package SPSS version 25.0.IBM was used. Thus, from the statistical analysis, the following results were obtained: 41.2% and 23.5% (higher percentages) unstable and avoidant personality types were observed. Moreover, 64.7% presented very high somatic anxiety 48 hours before the competition and very high cognitive anxiety with 82.4%. Consequently, two hours before the competition very high somatic anxiety was observed with 76.5% and very high cognitive anxiety with 88.2%. Therefore, it is necessary to take into account the little or non-existent psychological attention that our athletes receive.